The role of purchase intention in mediating the effect of perceived price and perceived quality on purchase decision - Satriawan, Kadek Aria; Setiawan, Putu Yudi (International research journal of management, IT and social sciences, 2020)
The study was aimed to explain the role of purchase intention in mediating perceived price and perceived quality of purchase decisions of Xiaomi Smartphone customers in Denpasar City. The sample is taken by a purposive sampling method as much as 130 Xiaomi customers in Denpasar. The Partial Least Square (PLS) analysis technique was applied. The result found that both perceived price and perceived quality positively and significantly affect purchase intentions and purchase decisions of Xiaomi smartphones. Furthermore, the role of purchase intention also significantly mediated the perceived price and perceived quality towards the Xiaomi smartphone purchase decision. This implies that the company should convince that the Xiaomi smartphone is worth the price, continue to improve the latest features to be more powerful and increasing the number of Xiaomi service centers in Indonesia, especially in the city of Denpasar.